Judicious distribution of laser emitters to shape the desired far-field patterns - Valagiannopoulos, Constantinos; Kovanis, Vassilios (PHYSICAL REVIEW A, 2017)
In this paper, motivated by such trends in coupled optical oscillators and applied mathematics methods, we inject an inverse-design approach in the construction of the far field of multiple radiating optical apertures. We consider the simple case of a one-dimensional array of equispaced photonic emitters and confine our study to the maximal radiation plane...
Keywords: laser; Research Subject Categories::NATURAL SCIENCES::Physics; physics